Quo Vadis : Kebijakan Politik Hukum Bank Syari’ah Pasca Undang-Undang Nomor 21 Tahun 2008 Tentang Perbankan Syariah - Rahmadi Indra Tektona (STIH Putri Maharaja, 2023)
The existence of legal politics in Islamic banks comprises the most common method for creating and enforcing regulations that can illustrate the kind and course in which the law will be constructed and implemented on the grounds. This is because the definition of legal politics itself is the official direction that the state uses as a basis to create and implement laws to achieve state goals. There are two dimensions of legal politics to consider when studying regulation: the basic policy dimension of why regulation is promulgated and the policy dimension of enactment. Regulations must be able to provide a basis and respond to the absence of the necessary supporting institutions for the Sharia banking industry, which serves as a form of improvement and implementation of the process of transforming the system of Islamic law into an integral part of the national legal system and laws regarding the operational system of banking business activities. The participation of Islamic banks in Indonesia is an important factor in national growth. This study employs an analytical-descriptive approach. It is a study that uses the statutory approach and the conceptual approach to define the scope and assess its existence. The formulation problem of this study is Quo Vadis: The Legal Politics of Islamic Banks under Post-Law Number 21 of 2008 on Sharia Banking. The purpose of this study is to examine the role of the state in regulating the development of Sharia banking in the context of the Plan to Create a Law on Sharia Economics.